Geological investigations of the sites of lithothamnian limestone in the area between Brezno and Savinja - Strgar, Ivan (Geologija, 2003)
In the area between Brezno and Savinja, detailed geological investigations and geological prospecting of ten lithothamnian limestone deposits were carried out according to the program of investigations in 1991 and 1992. Those sites were: • In the north, partly in the extraction area of former Laško colliery, with deposits Brezno - Bezoviški hrib, west of Gornje Brezno, between Gornje Brezno and Govce, Govški hrib, Trnov hrib, between Liša shaft and Barbara level, between Barbara level and Konjušnica, Brdo and Podšmihel. Western sites lie in the area belonging to the Hrastnik Municipality, but mostly in the area belonging to the Laško Municipality • In the south the area of Turski les, which belongs to the Hrastnik Municipality The objective of the investigations was to establish reserves and resources of lithothamnian limestone for the purposes of construction industry. The limestone should be extracted according to a special program of substitutional activities after the Laško mine will be closed. In the area Brezno - Brezoviški hrib detailed geological investigations were made, while in other nine areas only geological prospecting and assessment of the resources of lithothamnian limestone were carried out. Each of the investigated areas was assessed from the point of view of natural and economic indicators, such as: quantity of reserves and resources of lithothamnian limestone with preliminary evaluation of quality, usability, access and urban parts, possible impacts on narrow and wide surroundings, environment and usability of rock and aggregate. The results of the investigations pointed out three deposits as potentially interesting and perspective: between the Barbara shaft and Konjušnica, Brdo and Turski les. Other deposits were classified either as deposits with limited reserves and resources of lithothamnian limestone, or as non-perspective due to different limitations.